The Impact of Professional Learning Community and Collaboration in Higher Education - Vass, Vilmos (R&E-SOURCE, 2018)
The paper introduces the redesigning of university, especially focusing on the different types and levels of collaboration in higher education (HE). Based on the conceptual changes and some models of universities, two parts were built in the lecture. The first part describes contextual background of the topic, e.g. knowledge economy, revised concept of learning, teaching and knowledge. The second part analyses some features of Professional Learning Community (PLC), especially interdisciplinarity, sharing and change. The paper concludes with some dilemmas and questions for understanding the impact of PLC and collaboration in HE.